The horsewoman : a novel - Patterson, James, 1947-; Lupica, Mike (New York : Little, Brown, and Company, 2022)
Maggie Atwood and Becky McCabe, mother and daughter, both champion riders, vowed to never, ever, go up against one another. Until the tense, harrowing competitions leading to the Paris Olympics. Mother and daughter share a dream: to be the best horsewoman in the world.
Keywords: Horsemen and horsewomen -- Fiction; Show jumping -- Fiction; Olympics -- Fiction; Horse sports -- Fiction; Mothers and daughters -- Fiction; Horses -- Fiction; Sports fiction; Animal fiction; Thrillers (Fiction); Romance fiction; Large type books